Preliminary Analysis of Earthenware Production from the Shwe Creek Excavation in Bagan - Saw Tun Lin; Khin Kyi Phyu Thant; Moe Sat Wathan (The Journal of the Siam Society, 2025)
This article analyzes earthenware sherds from Shwe Creek (Operation 315a, Unit 315a–1) in Bagan, Myanmar, as part of the IRAW@Bagan project. Focusing on diagnostic rim sherds from the 2019 excavation season, the research employs typological classification and seriation to establish a preliminary chronological framework. Findings suggest a high degree of standardization in pottery production, particularly for utilitarian ceramics, and highlight both elite-controlled (attached) and market-driven (independent) production modes. Despite limited data, this preliminary archeological report provides a foundation for future ceramic research and relative dating of historical sites, emphasizing the need for continued analysis of Bagan’s earthenware traditions.